2013
DOI: 10.1042/bj20131020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of trehalase expression inhibits apoptosis in diapause cysts ofArtemia

Abstract: Trehalase, which specifically hydrolyses trehalose into glucose, plays an important role in the metabolism of trehalose. Large amounts of trehalose are stored in the diapause encysted embryos (cysts) of Artemia, which are not only vital to their extraordinary stress resistance, but also provide a source of energy for development after diapause is terminated. In the present study, a mechanism for the transcriptional regulation of trehalase was described in Artemia parthenogenetica. A trehalase-associated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…These observations certainly do not preclude apoptosis in these embryos, because the extrinsic pathway to apoptosis, activated through ligation of death receptors located in the plasma membrane, frequently serves as a mechanism to eliminate cells during development, differentiation, and tissue remodeling, as tissues are removed and replaced (81). Under certain experimental conditions with selective protein knockdown, terminal deoxynucleotidyl transferase dUTP nick end labeling assays have shown apoptosis to occur in developing embryos of A. franciscana (110,202,204). It is, nevertheless, interesting that during energy-limited states like diapause and anoxia, these embryos survive for months to years without apoptosis.…”
Section: Crustaceansmentioning
confidence: 95%
“…These observations certainly do not preclude apoptosis in these embryos, because the extrinsic pathway to apoptosis, activated through ligation of death receptors located in the plasma membrane, frequently serves as a mechanism to eliminate cells during development, differentiation, and tissue remodeling, as tissues are removed and replaced (81). Under certain experimental conditions with selective protein knockdown, terminal deoxynucleotidyl transferase dUTP nick end labeling assays have shown apoptosis to occur in developing embryos of A. franciscana (110,202,204). It is, nevertheless, interesting that during energy-limited states like diapause and anoxia, these embryos survive for months to years without apoptosis.…”
Section: Crustaceansmentioning
confidence: 95%
“…When A. pernyi larvae perceive unfavourable environmental signals, such as short daylengths or low temperatures, they are programmed to enter a stage of facultative diapause during their pupal development [ 10 ]. As trehalose is a major circulating sugar, and also serves as an agent protecting individuals against environmental stress, its concentration is closely related to the occurrence, maintenance, and termination of diapause in many insect species [ 11 , 12 , 13 , 14 , 15 ]. Previous studies have reported that trehalose accumulates in diapause-destined A. pernyi pupae, and relatively high trehalose levels are maintained throughout the diapause phase; however, these levels decrease significantly after diapause termination, suggesting close regulation of the level of trehalose from the onset to the termination of diapause [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The need for a termination cue differentiates diapause from quiescence, a hypometabolic, stress-tolerant state requiring only return to favorable growth parameters for termination (Drinkwater and Clegg 1991). Stress tolerance during diapause and quiescence in Artemia has been examined from several perspectives including the synthesis, composition, and structure of the cyst shell (Liu et al 2009;Dai et al 2011a;, the role of trehalose (Clegg 1965;Clegg and Jackson 1992;Yang et al 2013), the composition and activity of late embryogenesis abundant (LEA) proteins (Sharon et al 2009;Wu et al 2011;Toxopeus et al 2014), and the function of molecular chaperones such as small heat shock proteins (sHsps) and artemin (King and MacRae 2012;King et al 2013King et al , 2014.…”
Section: Introductionmentioning
confidence: 99%